Analysis of Load and Lubrication State of Racks and Pinions of Three Gorges Ship Lift Based on Actual Service Conditions - Chen Zhuo; Shi Lubing; Feng Panpan; Li Xuefei; Chen Lin; Liu Zhongming (Jixie chuandong)
The rack and pinion of the three gorges ship lift is a low speed and heavy load open gear transmission with hard tooth surface. Once the lubrication is poor, it is easy to cause damage such as tooth surface scuffing, which will affect the operation safety and reliability of the ship lift. This study is based on the actual operation data of the three gorges ship lift, and the lubrication of racks and pinions under various typical service conditions is systematically analyzed using the oil film thickness criterion. The relationship between the false water depth and the film thickness ratio in the ship compartment is deduced and the film thickness ratio of the lubrication state of the most dangerous meshing point under typical false water depth is calculated when the ship compartment is under constant speed. The worst lubrication condition of the rack and pinion is determined when the ship compartment is ascending and descending with variable speeds, and the relationship between the water depth in the ship compartment and the lubrication condition under variable speed typical operating conditions is analyzed. The position where the scuffing damage is more likely to occur is further determined. The results show that, when the ship lift is running at a constant speed, the lubrication state of the rack and pinion is the best under the optimum water depth in the ship compartment, and the film thickness ratio of the deviation from the optimal water level decreases with the power function <alternatives>λ∝±Δh-0.13 <?fx-imagestate width="18.79599953" height="3.04800010"?> <?fx-imagestate width="18.79599953" height="3.04800010"?> </alternatives> of the false water depth. When the rack and pinion is at the most dangerous meshing point, the root of the pinion and the top of the rack are in contact, and the lubrication condition between tooth surfaces is worse under large false water depth. When the ship lift moves at variable speeds, the working condition with poor lubrication condition is the upward acceleration and downward deceleration when the water depth of the ship chamber is 3.6 m. Due to the high contact frequency of the upper tooth surface on the rack and poor lubrication state, the risk of scuffing damage is higher.